PENGARUH GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI: Studi Pada Rumah Sakit Umum Daerah Nyitdah - I Putu Santika; Ni Luh Gede Era Puspita Dewi; Ni Luh Sili Antari; I Gede Adindya Perdana Putra (Journal of Applied Management Studies, 2023)
This study aims to analyze the effect of leadership style and organizational climate on employee performance through job satisfaction as a mediating variable (study at Nyitdah Regional General Hospital). The data analysis technique uses 'path analysis' (path analysis) where the data has been tested for validity, reliability test, and classical assumption test. The results of the analysis found that 1) Leadership style has a positive and significant effect on employee job satisfaction at Nyitdah Hospital; 2) Organizational climate has a positive and significant effect on employee job satisfaction at Nyitdah Hospital; 3) Leadership style has a positive and significant effect on employee performance at Nyitdah Hospital; 4) Organizational climate has a positive and significant effect on employee performance at Nyitdah Hospital; 5) Job satisfaction has a positive and significant effect on employee performance at Nyitdah Hospital; 6) Leadership style has a positive effect on employee performance through job satisfaction at Nyitdah Hospital. Job satisfaction has not been able to act as a mediating variable in the relationship between leadership style and employee performance at Nyitdah Hospital; and 7) Organizational climate has a positive and significant effect on employee performance through job satisfaction at Nyitdah Hospital. Job satisfaction can act as a mediating variable in the relationship between organizational climate and employee performance at Nyitdah Hospital. Suggestions in this study, it is expected that the hospital director should maintain and improve leadership style, organizational climate, and job satisfaction to improve employee performance.